A Growth-Learning Perspective Measurement of PT. Eastern Pearl Flour Mills Staff Performance - Anne Abdurrahman; Khaeriyah Khaeriyah; Nurmadhani Fitri Suyuthi; Nurasia Natsir (International Journal of Economics, Business and Innovation Research, 2023)
The study's goal is to quantify PT's effectiveness. Eastern Pearl Flour Mills employs the Balanced Scorecard method for learning and growth. This study employs a combination of methods. Data was gathered from company reports and research documents, as well as by distributing questionnaires to PT employees and customers. East Pearl Flour Factory in Makassar. A questionnaire was used to collect data based on the number of samples specified. Increasing employee engagement in training is indicative of positive outcomes from a learning and development standpoint. This is done to improve employee performance while also setting high expectations for the workplace and lowering employee absenteeism. On the basis of the distribution of the satisfaction and learning index questionnaires, which were given to employees, the results of the two questionnaires show that they are in the agree category. This indicates that employees like the services that the company provides to them and that they agree with the efforts that the company makes. It is the responsibility of the company to look after its employees. Employees rate the company highly because the results of the questionnaire distribution show a scale on an agreed-upon scale based on good standards.